The wellbeing effects of an old age pension: Experimental evidence for Ekiti State in Nigeria - María Laura Alzúa; Natalia Cantet; Ana C. Dammert; Damilola Olajide (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2023)
Many countries in the developing world have implemented old-age pensions. Evidence of the impact of such policies on the elderly in sub-Saharan Africa, however, is scarce. We provide evidence from a randomized evaluation of an unconditional old-age pension targeted at the elderly in Ekiti State, Nigeria. Our findings show that treated beneficiaries self-report better quality of life and a more stable mental health. We also provide evidence of spillover effects on the labor outcomes of other household members and of household savings patterns as well as support for interventions aimed at improving the welfare of elderly poor citizens and other household members.
Keywords: C21; C93; H31; H55; H75 I38; 330; randomized controlled trials; aging; old-age pensions; health; developingcountries